Whole person care, patient-centred care and clinical practice guidelines in general practice. Issue 2 (3rd May 2016) - Hansen, Emily; Walters, Julia; Howes, Faline
ABSTRACT: Clinical practice guidelines (CPGs) are a central technique within the evidence-based medicine (EBM) movement. General practice is an area of medicine that seems to be particularly resistant to the use of CPGs. This article contributes to the debates about GPs and CPGs by reflecting on three different Australian studies conducted by the authors in an attempt to better understand variations between GPs' practices and the recommendations found in relevant CPGs. These projects focused on dementia, chronic obstructive pulmonary disease and hypertension (high blood pressure). A common finding across the three studies was that GPs described how their focus on the whole person and their patients' priorities and needs meant that the recommendations found in CPGs were not always appropriate or easy to apply. In doing this, our study participants were describing tensions between the holistic/whole person and patient-centred approach of GPs and the narrow disease-specific focus of guidelines. Our work provides insight into the rationality of GPs and illustrates some of the ways that whole person care and patient-centred care create operational challenges to the application of EBM in the form of CPGs.